2012
DOI: 10.1002/app.38544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEO on the network structure of PVA hydrogels prepared by freezing/thawing method

Abstract: Poly(vinyl alcohol) (PVA)/poly(ethylene oxide) (PEO) hydrogels were prepared by freezing/thawing method for application as a wound dressing. The effect of PEO content on the network structure of PVA hydrogel was investigated in terms of crystalline and reological properties. It was found that a low amount of PVA crystallites were present in PVA/PEO hydrogels. With increasing content of PEO, the crstallinity of PVA hydrogel decreased, but the apparent dimensions of crystallites increased. The shear storage modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…We can therefore exclude that PEO can compete with the vinyl alcohol units for reacting with borate ions. From literature studies it is known that PEO acts as a porogen agent in PVA/borax membranes [23] and in PVA gels obtained with freezing/thawing method [24]. In the latter work is reported that addition of PEO in a PVA/water system causes the decrease of PVA degree of crystallinity resulting in the increase of network mesh size and decrease of the storage modulus.…”
Section: Rheological Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…We can therefore exclude that PEO can compete with the vinyl alcohol units for reacting with borate ions. From literature studies it is known that PEO acts as a porogen agent in PVA/borax membranes [23] and in PVA gels obtained with freezing/thawing method [24]. In the latter work is reported that addition of PEO in a PVA/water system causes the decrease of PVA degree of crystallinity resulting in the increase of network mesh size and decrease of the storage modulus.…”
Section: Rheological Characterizationmentioning
confidence: 95%
“…In the present study we have investigated the effect of adding poly(ethyleneoxide) (PEO) in various concentrations on the mechanical properties of PVA/borax gels and its influence on the capability of retaining organic solvents. PEO is a water-soluble and biocompatible thermoplastic polymer and the literature suggests that it causes an increment of the pores size in PVA/borax hydrogels [23,24] with increasing, at the same time, the mechanical properties. For the above reasons PEO could be a suitable additive for improving the physical characteristics of PVA/borax hydrogels, and possible positive interactions with the miscible organic solvents used in conservation applications.…”
Section: Introductionmentioning
confidence: 99%
“…So the degree of crystallinity has an effect on the crosslink density in polymer network. 41 As a consequence, relatively high crystallinity of oriented scaffold reveals a more compact network structure in polymeric matrix to accommodate water. Generally, the scaffold should possess the ability to sustain the structural integrity under certain compression, which is necessary to protect the cells or neo-tissue within scaffold from damage.…”
Section: Characterization Of Scaffoldsmentioning
confidence: 99%
“…The test methods employed were oscillatory frequency sweep [14]. The hydrogels were subjected to a frequency sweep in the range from 0.01 to 100 Hz at a fixed shear stress (10 Pa) and temperature (25°C).…”
Section: Rheological Evaluationmentioning
confidence: 99%